Jesse - Soto, Gary. (San Diego : Harcourt Brace, 1994)
Two Mexican American brothers hope that junior college will help them escape their heritage of tedious physical labor.
Keywords: Mexican Americans -- Juvenile fiction; Mexican Americans -- Fiction; Brothers -- Fiction; Universities and colleges -- Fiction